ONLINE ROOM ALLOCATION SYSTEM WITH ROOM KEY VENDING MACHINE FOR COLLEGE IN UNIMAS - Low, Wei Mei (Universiti Malaysia Sarawak (UNIMAS), 2020)
Online room allocation system with room key vending machine for college in UNIMAS is a system which allows students to make room registration and receive room key without approach to college of ice. This proposed system can help to reduce the problem faced by students such as long line queuing during room registration. At the same time, the proposed system also able to improve current manual room allocation system into computerized system. Through the proposed system, students can make room reservation due to personal reason such as healthy problem. Then, staff can filter their reservation application and assigned the most suitable room for them based on their condition. The methodology which had implemented in this proposed system is waterfall Model. Each phase in the model have their own tasks and different goal which contribute to the formation of the proposed system.